Implementasi NDP: Cara Mudah Menunjang Mutu Kepribadian dalam Kehidupan Sosial - Anugrah C. Pratama (STAI DDI Kota Makassar, 2020)
Religious maturity is a major effort to realize the harmony of religious life in Indonesia. HMI with its Basic Values ​​of Struggle is the starting point in developing, disseminating and implementing such religious maturity. At the very least, in the Basic Values ​​of the HMI Struggle there are three aspects to realizing the quality of personality in social life, namely: the aspect of oneness (Divinity of the One), the aspect of humanity and the aspect of society, harmonious.